PENGETAHUAN, SIKAP DAN PERILAKU ORANG TUA TENTANG KEKERASAN FISIK PADA ANAK DI PAPUA. - Noni Yoimo; Tri Ismu Pujiyanto; Witri Hastuti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Children are an asset for a country that would become the next generation for development . Due to the lack of knowledge of their parents , children who should be protected , often getting rough treatment from the people around him . Currently family violence is recognized as one of the public health problem . Cases of violence against children continues to increase from year to year . Child protection data showed cases of violence in Papua in 2010 was 481 cases . This number increased to 547 cases in 2011 , of which 221 cases were sexual abuse , 140 physical violence ,psychological violence 80 % , and 106 other issues . The purpose of this study was to determine the relationship between knowledge , attitudes , behaviors parents about prevention of physical violence against children . This research is a descriptive cross sectional correlation . The samples used were citizens of District East Paniai , Papua , with a total sample of 130 respondents , the sampling technique used by using purposive sampling method . Results of univariate analysis showed that most of the people have the knowledge , attitude and behavior towards the prevention of violence against children . The results of bivariate analysis showed that knowledge and attitudes are closely related to the behavior of the parents . The problem of child abuse is not a stand-alone issue but is influenced by several interacting factors . For further research is recommended to look at other variables such as parenting , culture , personality actorsto be associated with the phenomenon of violence in children .